1989
DOI: 10.1063/1.456571
|View full text |Cite
|
Sign up to set email alerts
|

Rotation–vibration spectra of icosahedral molecules. II. Icosahedral symmetry, vibrational eigenfrequencies, and normal modes of buckminsterfullerene

Abstract: The icosahedral symmetry of molecules such as buckyball, B12H12−2, and C20H20, is analyzed using subgroup chain defined projection operators. The icosahedral analysis is used to determine the eigenvalues and eigenvectors of a classical spring mass model of buckyball. A spectrum of Raman and dipole active modes is given using the spring constants of benzene. Corresponding dipole active and Raman active normal modes are displayed stereographically. Several choices for springs constants are discussed and a compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(72 citation statements)
references
References 21 publications
4
67
0
1
Order By: Relevance
“…is the laser frequency, and is the ellipticity. We treat C z 60 as a classical spring-mass network in a similar manner as has been used to analyze the rotation-vibration spectrum of neutral C 60 [23]. We use their simplification that associates a single force constant, h, with the stretching of both the single and the double bonds and a single force constant, , that describe C-C-C and C-C=C bending.…”
mentioning
confidence: 99%
“…is the laser frequency, and is the ellipticity. We treat C z 60 as a classical spring-mass network in a similar manner as has been used to analyze the rotation-vibration spectrum of neutral C 60 [23]. We use their simplification that associates a single force constant, h, with the stretching of both the single and the double bonds and a single force constant, , that describe C-C-C and C-C=C bending.…”
mentioning
confidence: 99%
“…Hence only T 1u modes can be first-order IR active in pure C 60 . For two-quantum absorption, the selection rules for either the secondorder dipole moment mechanism (16) or the first-order dipole moment plus cubic anharmonicity mechanism are the same: two modes f and f cannot be second-order active unless their direct product representation Γ f × Γ f includes the representation r. For pure C 60 , the resulting possible combination mode symmetry types are listed in Table 1. Table 1.…”
Section: Symmetry and Selection Rulesmentioning
confidence: 99%
“…It is found that the number of linearly independent times each irreducible representation appears is 2(A g ), 1(A u ), 4(T 1g ), 5(T 1u ), 4(T 3g ), 5(T 3u ), 6(G g ), 6(G u ), 8(H g ), and 7(H u ). The notation is that of Weeks and Harter [16], who provide a detailed account of the icosahedral group and its application to the harmonic vibrations of C 60 . The irreducible representations of types A, T, G, and H are of dimensionalities 1, 3, 4, and 5, respectively, these giving the degeneracies, while the g and u subscripts specify the representations for even and odd modes.…”
Section: Symmetry and Selection Rulesmentioning
confidence: 99%
See 2 more Smart Citations